Fuzzy object functional dependences in fuzzy object-oriented databases. - Ban, Đoàn Văn; Hà, Hồ Cẩm; Quảng, Võ Đức (Journal of Computer Science and Cybernetics, 2012)
In this article, we propose fuzzy object functional dependences which allow to express constraints on attributes of arbitrary object types including the types themselves. Different semantics of fuzzy object functional dependency (FOFD) relating to the validity of a fuzzy object-oriented database schema state for a FOFD are introduced and discussed. FOFDs are considered as one of the tools to identify fuzzy objects in fuzzy object-oriented databases